Open Social Knowledge Creation and Library and Archival Metadata. Issue 1 (27th February 2019) - Seeman, Dean; Dean, Heather
Standardization both reflects and facilitates the collaborative and networked approach to metadata creation within the fields of librarianship and archival studies. These standards—such as Resource Description and Access and Rules for Archival Description—and the theoretical frameworks they embody enable professionals to work more effectively together. Yet such guidelines also determine who is qualified to undertake the work of cataloging and processing in libraries and archives. Both fields are empathetic to facilitating user-generated metadata and have taken steps towards collaborating with their research communities (as illustrated, for example, by social tagging and folksonomies) but these initial experiments cannot yet be regarded as widely adopted and radically open and social. This paper explores the recent histories of descriptive work in libraries and archives and the challenges involved in departing from deeply established models of metadata creation.